Temperature as a likely driver shaping global patterns in mineralogical composition in bryozoans: implications for marine calcifiers under global change. Issue 1 (25th November 2022) - Figuerola, Blanca; Griffiths, Huw J.; Krzeminska, Malgorzata; Piwoni‐Piorewicz, Anna; Iglikowska, Anna; Kuklinski, Piotr
Abstract : The Southern Ocean is showing one of the most rapid responses to human‐induced global change, thus acting as a sentinel of the effects on marine species and ecosystems. Ocean warming and acidification are already impacting benthic species with carbonate skeletons, but the magnitude of these changes to species and ecosystems remains largely unknown. Here we provide the largest carbonate mineralogical dataset to date for Southern Ocean bryozoans, which are diverse, abundant and important as carbonate producers, thus making them excellent for monitoring the effects of ocean warming and acidification. To improve our understanding of how bryozoans might respond to ocean warming and acidification, we assess latitudinal and seafloor temperature patterns of skeletal mineralogy using bryozoan species occurrences together with temperature data for the first time. Our findings, combining new mineralogical data with published data from warmer regions, show that the proportions of high‐Mg calcite and bimineralic species increase significantly towards lower latitudes and with increasing seawater temperature. These patterns are consistent with the hypothesis that seawater temperature is likely a significant driver of variations in bryozoan mineralogy at a global scale.